Lower-limb muscular strategies for increasing running speed - Schache, A. G.; Dorn, T. W.; Williams, G. P.; Brown, N. A. T.; Pandy, M. G. (Journal of Orthopaedic & Sports Physical Therapy, 2014)
This clinical commentary discusses the mechanisms used by the lower-limb musculature to achieve faster running speeds. A variety of methodological approaches have been taken to evaluate lower-limb muscle function during running, including direct recordings of muscle electromyographic signal, inverse dynamics-based analyses, and computational musculoskeletal modeling. Progressing running speed from jogging to sprinting is mostly dependent on ankle and hip muscle performance. For speeds up to approximately 7.0 m/s, the dominant strategy is to push on the ground forcefully to increase stride length, and the major ankle plantar flexors (soleus and gastrocnemius) have a particularly important role in this regard. At speeds beyond approximately 7.0 m/s, the force-generating capacity of these muscles becomes less effective. Therefore, as running speed is progressed toward sprinting, the dominant strategy shifts toward the goal of increasing stride frequency and pushing on the ground more frequently. This strategy is achieved by generating substantially more power at the hip joint, thereby increasing the biomechanical demand on proximal lower-limb muscles such as the iliopsoas, gluteus maximus, rectus femoris, and hamstrings. Basic science knowledge regarding lower-limb muscle function during running has implications for understanding why sprinting performance declines with age. It is also of great value to the clinician for designing rehabilitation programs to restore running ability in young, previously active adults who have sustained a traumatic brain injury and have severe impairments of muscle function (eg, weakness, spasticity, poor motor control) that limit their capacity to run at any speed.